2009
DOI: 10.1146/annurev.fluid.010908.165232
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Vortex Formation as a Unifying Principle in Biological Propulsion

Abstract: I review the concept of optimal vortex formation and examine its relevance to propulsion in biological and bio-inspired systems, ranging from the human heart to underwater vehicles. By using examples from the existing literature and new analyses, I show that optimal vortex formation can potentially serve as a unifying principle to understand the diversity of solutions used to achieve propulsion in nature. Additionally, optimal vortex formation can provide a framework in which to design engineered propulsions s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
178
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(200 citation statements)
references
References 61 publications
21
178
1
Order By: Relevance
“…16,17,34 The concept of vortex formation time (VFT) appeared as a potentially relevant indicator in the assessment of LV functionality, being related to the dynamical properties of the intraventricular flow and valvular motion. 45,48,49 Subsequent studies on VFT evidenced its alteration in patients with diastolic dysfunction as well in those with dyskinetic regions.…”
Section: First Studies On Vortex Formationmentioning
confidence: 99%
“…16,17,34 The concept of vortex formation time (VFT) appeared as a potentially relevant indicator in the assessment of LV functionality, being related to the dynamical properties of the intraventricular flow and valvular motion. 45,48,49 Subsequent studies on VFT evidenced its alteration in patients with diastolic dysfunction as well in those with dyskinetic regions.…”
Section: First Studies On Vortex Formationmentioning
confidence: 99%
“…13,14 This has been the subject of recent and ongoing research because a formation time of T Ϸ 4 has been observed in many vortex generating devices. 13 For example, such a vortex formation time was first observed in piston-cylinder vortex ring generators, 14 but the same T Ϸ 4 was also observed in flow over a cylinder 15 and over flapping wings. 16 Under the current setup, the vortex formation time is defined as…”
Section: -9mentioning
confidence: 99%
“…Earlier studies have described vortex formation in terms of one-directional transmitral flow profiles 7,14 and the movement and rotation of the vortex ring core 13,19 . In a recent review, Dabiri suggested that the volume of the vortex ring is an important property of vortex ring formation, since a large vortex ring can transport a large amount of blood into the LV during diastole efficiently and without forming a turbulent jet 2 . Additionally, the vortex ring may enhance recoil of the atrioventricular plane towards the base of the heart during rapid filling 17 .…”
Section: Introductionmentioning
confidence: 99%